STRATEGI PENINGKATKAN MUTU PERGURUAN TINGGI AGAMA KATOLIK MELALUI TRANSFORMASI MANAJEMEN SUMBER DAYA MANUSIA - Hamu, Fransiskus Janu (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2016)
The purpose of this paper is to examine the situation and condition of theCollegeâs Catholic religion. Based on observations and experiences as a personwho was involved in organizing the Catholic religion, the College encouragesauthors to offer the concept of management development College Catholicreligion with a focus on the development of the human resource managementof College Catholicism. The author believes that human resources be onedetermining factor of a collegeâs quality.